Effects and Outcomes of Temporomandibular Joint Due to Wisdom Tooth Extraction - Hussain, Hamd Ali; Arooj, Ayesha; Shakeel, Hammad; Tauqeer, Sana; Saleem, Sidra; Hussain, Syed Zahid (Pakistan Armed Forces Medical Journal, 2024)
Objective: To find out the effects and outcomes of temporomandibular joint due to wisdom tooth extraction. Study Design: A cross sectional study. Place and Duration of Study: University of Lahore Teaching Hospital and Lahore Dental Clinic, Lahore Pakistan, from May to Oct 2020. Methodology: A total of 58 people were included in the study. Convenient sampling technique was used. The Temporomandibular Joint Disability Index Questionnaire was used to assess the extent of disability following wisdom tooth removal. The patients with wisdom tooth extraction minimum six months ago were included. Results: Among the participants, 35 and 23 were males and females respectively in between age of 17-30 years with mean age of 23±3.21 years. These statistically significant results with communication by yawning or mouth opening which indicated difficulty in speaking after wisdom tooth extraction. Other factors were found with no effect on temporomandibular joint such as brushing or flossing, eating etc. Conclusion: The individual’s responses in their activities of daily life to communication and yawning or mouth opening were found statistically significant on temporomandibular joint disability index.